Enhancing Student Creativity through Smartphone Photography Workshops: A Case Study at STAIN Madina - Ahmad Salman Farid (Mangabdi: Journal of Community Engagement in Religion, Social, and Humanities, 2024)
The digital era has made photography an essential skill, especially with the advancement of smartphone technology, enabling users to produce high-quality photos. However, many students have yet to understand how to optimally utilize camera features. This program aims to enhance the creativity of STAIN Madina students through smartphone photography training. This community service activity employs the Participatory Action Research (PAR) method, involving students in all stages of the activity: planning, implementation, and evaluation. The training was conducted over three days, covering basic photography theory, field practice, and digital portfolio development. Evaluation was carried out through pre-tests, post-tests, and an exhibition of participants' works. The training successfully improved the students' photography skills. A total of 85% of participants demonstrated improved photography outcomes after the training. Additionally, participants were able to create digital portfolios to showcase their works. Satisfaction surveys revealed that 90% of participants found the training beneficial for developing their creative and professional skills. The results indicate that the PAR approach is effective in increasing participant engagement, which positively impacts their skills and creativity. The training not only provided technical benefits but also opened new opportunities for students to utilize photography as a medium of expression and a potential career path.